IMPROVE, a community‐based exercise intervention versus support group to improve functional and health outcomes among older African American and Non‐Hispanic White breast cancer survivors from diverse socioeconomic backgrounds: Recruitment strategies and baseline characteristics. Issue 11 (4th February 2021) - Owusu, Cynthia; Nock, Nora L.; Feuntes, Vanessa; Margevicius, Seunghee; Hergenroeder, Paul; Austin, Kristina; Bennet, Elizabeth; Cerne, Stephen; Moore, Halle C. F.; Petkac, Jean; Schluchter, Mark; Schmitz, Kathryn H.; et al.
Abstract : Background: Behavioral intervention studies in older breast cancer survivors, particularly older African American (AA) and socioeconomic status–disadvantaged breast cancer survivors, are lacking. To inform future studies, the authors examined recruitment strategies in older breast cancer survivors who participated in an exercise intervention study. Methods: IMPROVE is a randomized trial designed to evaluate a group‐based exercise intervention versus a support group (ClinicalTrials.gov identifier, NCT02763228). Participants were aged ≥65 years who had survived stage I through III breast cancer and were within 5 years of treatment completion. Participants were recruited through multiple approaches, including peripheral, linguistic, and constituent‐involving strategies that incorporated the identification of potentially eligible patients from 3 local hospitals and from State of Ohio registries and through direct clinician and community organization referrals. Results: Between October 2016 and November 2019, 7487 patients were screened, 4790 were potentially eligible, and 213 were randomized into the study. The eligible:randomization rates were 4.4% overall and 84%, 8%, and 2% for recruitment using direct referrals, hospital registries, and state registries, respectively. The median age of the randomized cohort was 70 years (range, 65‐88 years) and included 44% AA and 44% socioeconomic status–disadvantaged breast cancer survivors. Compared with all registry‐eligible patients, directly referred‐eligible patients were more likely to be AA versus Non‐Hispanic White (41% vs 19%; P = .006), to be contacted successfully (100% vs 33%; P < .0001), and to accept study participation (88% vs 16%; P < .0001). Conclusions: Direct referrals appeared to be the most efficient strategy for recruiting AA survivors. Behavioral intervention studies seeking to target older AA and socioeconomic status–disadvantaged breast cancer survivors should include strategies that foster direct referrals to study participation. Abstract : Although multiple strategies for recruitment are needed, direct referrals are particularly effective for recruiting older African American breast cancer survivors into behavioral intervention studies. Studies seeking to target older breast cancer survivors from racial minority and socioeconomically disadvantaged backgrounds should devote their efforts and resources to strategies that foster direct referrals to study participation, including the use of constituent‐involving strategies and fostering close partnerships with providers and community leaders.